Molecular Characterization Clinical and Immunotherapeutic Characteristics of m5C Regulator NOP2 Across 33 Cancer Types - Liu, Taisheng; Zhang, Jian; Lin, Chunxuan; Liu, Guihong; Xie, Guofeng; Dai, Zili; Yu, Peng; Wang, Jian; Guo, Liyi (Frontiers in Cell and Developmental Biology, 2022)
Background: Recent studies have identified that RNA 5-methylcytosine (m5C) is a wide spread epigenetic modification in tumorigenesis. However, the clinical and immunotherapeutic value on m5C regulator NOP2 in 33 cancers remain unclear. Methods: The mRNA expression data and clinical data of 33 cancers were downloaded from the Cancer Genome Atlas Database (TCGA). The immunotherapy data including GSE67501, GSE78220, GSE35640 and IMvigor210 were downloaded from the Gene Expression Omnibus (GEO) database and the website based on the Creative Commons 3.0 License (http://research-pub.Gene.com/imvigor210corebiologies). The expression, survival, clinical parameters, tumor mutation burden (TMB), microsatellite instability (MSI) and tumor microenvironment (TME) were evaluated. Finally, the relationship between NOP2 and immunotherapy response was further explored. Results: NOP2 was significantly upregulated in most cancers, and high NOP2 expression was associated with poor prognosis. TMB, MSI and NOP2 activity were involved in dysregulation of NOP2. NOP2 was closely associated with immune cell infiltration, immune modulators, and immunotherapeutic inactivation. Conclusions: We comprehensively explored the clinical and immunotherapeutic value of NOP2 in cancers, providing evidence regarding the function of NOP2 and its role in clinical treatment.